Role of compressed air energy storage in urban integrated energy systems with increasing wind penetration. (May 2022) - Xia, Tian; Li, Yaowang; Zhang, Ning; Kang, Chongqing
Abstract: Accelerated decarbonization agenda around the world requires transforming the energy industry from fossil fuel-dominated to renewable generation-dominated, which necessitates deployment of energy storage on a significantly larger scale. As a potential alternative for the most widely adopted pumped hydro storage, compressed air energy storage (CAES) is recognized as a promising component of energy sectors. Although numerous studies on CAES have contributed to the improvement of technical readiness, there are few studies on cost-effectiveness analysis to evaluate the role of CAES in urban integrated energy systems (IESs). To fill this gap, this paper proposes a planning-operation bi-level framework to evaluate the role of CAES in urban IES, and conducts an empirical study on a realistic urban IES of northern China. The cost-effectiveness of diabatic-CAES (D-CAES) and adiabatic-CAES (A-CAES) are compared in the empirical study. The results show that D-CAES can play an important role in urban IES and replace CHP as the core component to supply heat and power, reducing system overall cost and wind curtailment. The participation of D-CAES in the municipal heating sector is crucial to its superior role in urban IES. The role of A-CAES in the urban IES is relatively marginal in cases with low wind capacity and becomes more important with wind capacity increasing. Highlights: Operation characteristics of utility-scale D-CAES and A-CAES in urban IES are presented. A planning-operation bi-level framework is proposed to evaluate CAES's role in urban IES. Empirical study on an urban IES in northern China using real-life data. D-CAES can be more cost-effective than A-CAES in urban IES with heating supply.